From the field of offerings studies in memory of Lanny D. Bell - D'Auria, Sue; Lacovara, Peter (Lockwood Press, 2023)
"This Memorial volume honors the life and work of Prof. Lanny David Bell (April 30, 1941-August 26, 2019), a leading scholar in Egyptology and a beloved teacher and colleague to so many. It includes a biography of Dr. Bell along with contributions from eminent scholars on the topics of ancient art, archaeology, religion, and philology"--
Includes bibliographical references and index
2306
Keywords: Altertümer; Ägypten -- Altertum; Egypt / Antiquities; Aufsatzsammlung; Festschrift